Prevalence of vitamin D3 deficiency and its correlation with high-risk pregnancy pre-eclampsia and eclampsia study from central India - Nandedkar, Aditya Madhav; Bachewar, Paraji; Memon, Madiha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: To study the relationship between vitamin D3 deficiency and pre- eclampsia and eclampsia. Methods: It is case control study, The study was conducted in the department of medicine Pt. J. N. M. and BRAM hospital, Raipur (CG) among the patients diagnosed as pre-eclampsia and eclampsia admitted in Obs. and Gynae wards. Study group (Group A) comprised of 80 patients diagnosed as pre-eclampsia and eclampsia presented at term Control group (Group B) comprised of 50 individuals from normal healthy population (ANC patient at term which was normotensive) Results: It is case control study. In this study 130 patients were included of which study group comprised of 80 patients and control group comprised of 50 patients. it has been observed that vitamin D deficiency was prevalent among the study group and control group however statistically significant higher number of cases in study group (toxemia of pregnancy) were vitamin D deficient as compared to control group. In our study 95% cases had lower level of vitamin D (35% insufficient and 60% deficient) as compared to 72% (46% insufficient and 28% deficient) in control. Out of these 60% of cases in study group vs. 28% cases in control group were seriously vitamin D deficient (vitamin D level <30 nmol/l). Conclusions: Vitamin D deficiency and insufficiency was found to be associated with normal pregnancy (control group), preeclampsia and eclampsia. In present study direct correlation was observed in preeclampsia and eclampsia with low vitamin D levels.